Avaliação Comparativa de Diferentes Proporções das Misturas Diesel-Biodiesel-Etanol e Diesel-Biodiesel frente ao Diesel Tipo A :Análises Físico-Químicas e de Desempenho de um Conjunto Motor-Gerador - Klajn, Felipe Fernandes (2016)
The search for alternatives to reduce diesel within the national energy matrix, particularly within the transport sector, has been studied and carried out in a gradual manner with partial insertions of biodiesel to diesel. This binary mixture, however, can be improved by the addition of ethyl alcohol (ethanol), which contain oxygen atoms in its structure and may be able to promote more efficient burning and to reduce exhaust emissions, both sulfur and non-sulfur. This work aimed to evaluate the energy performance of an engine-generator set working with diesel-biodiesel blends and diesel-biodiesel-ethanol, compared with the diesel type "A", i.e, diesel without the addition of biodiesel, as well as physicochemical characteristics of each treatment. The diesel-biodiesel mixtures were based on the currently marketed formulation (B7) and projections provided by the Senate Bill 613/2015 and Resolution No. 3/2015 CNPE for captive consumers or road fleets, ie, B10, B15 and B20. Each binary mixture this has undergone additions of anhydrous ethanol (99.6% p / p) to 1%, 5%, 10% and 15%. The treatments were subjected to 5 resistive loads of 1, 2, 3, 4 and 5 kW in triplicate. The set of data collected, analyzed the density, viscosity, calorific value, specific consumption (CE), energy efficiency (EE) and SO2 emissions. The density and viscosity of the mixtures were close to the diesel and within the specifications of the National Agency of Petroleum, Natural Gas and Biofuels (ANP). The calorific value decreased as the biofuel incorporated into the diesel grew. The best specific fuel consumption was observed in absolute terms at a load of 5 kW for B15E1 with 327.1 g kW-1 h-1followed by B10E1 (330.1 g kW-1 h-1) and diesel (g kW-1 h-1). The ternary mixture composed by adding 1% ethanol did not differ statistically from diesel-biodiesel blends for all applied loads. The greatest EE of 27.15% was observed at the load of 4 kW, to B10E15 mixture. The B15E1 mixtures, B20E1 and B20E0 were more efficient than diesel for all applied loads. The lowest emission of SO2 was 5 kW for the load B10E0 with 397.66 ppm, while the highest was in load of 1 kW for B15E15 with 3391.67 ppm.